Implementasi Teori Penetrasi Sosial pada Pengguna Aplikasi Tinder - Alvin Gus Abdurrahman; Chairun Nisa Dwi Putri; Irwansyah Irwansyah (JURNAL LENSA MUTIARA KOMUNIKASI, 2021)
The Covid-19 pandemic has changed social behaviour in society. Especially in the process of building relationships with opposite sex, which is usually done face-to-face, is now turning online. This is the impact of the government's policy to limit large-scale social activities to prevent the development of the coronavirus. In 2020, the number of chat exchanges on the Tinder app increased by 23%. Nowadays people prefer to get to know others online before deciding to meet in person. Social Penetration Theory (TPS) can be used to analyse the process of communication and self-disclosure of an individual in building interpersonal relationships. This theory describes a person like an onion that has various layers in it because someone only provides general information in the early stages of a relationship then reveals more personal information when they get close and build trust. This research is different from previous work because it analyses TPS on Tinder application users during the Covid-19 pandemic. This study aims to review TPS on Tinder application users by testing the main assumptions of the theory in relationship development and self-disclosure. This study uses a qualitative approach. Data collection is done by searching for articles journals with keywords TPS and the use of Tinder application to build relationships. The results show that the self-disclosure mediated by digital technology can limit the general and personal information shared by its users. The limitation of it lies in the ability to read non-verbal messages. Gender factors influence how individuals build relationships in the early stages. Men tend to approach women aggressively using jokes or funny statements, while women rely more on subtle cues. Future research can focus on the communication of Tinder application users at different age ranges. This research is expected to be input for research on online communication, self-disclosure and relationship development.